The association of women’s empowerment dimensions and antenatal care utilization in Ethiopia; facility based cross-sectional study - Yonas Abebe; Asresash Demissie; Kebebe Adugna (BMC Women's Health)
Abstract Background Women’s empowerment is a multidimensional global development goal. Women in low-income countries are often disempowered, which can lead to increased mortality and morbidity by inhibiting their access to essential maternal health care, such as antenatal care. It is impossible to decrease maternal mortality without sufficient and timely antenatal care. However, the association between women’s empowerment and antenatal care utilization has been understudied. Therefore, this research aims to assess the association of women’s empowerment dimensions with antenatal care use. Method A facility-based cross-sectional study was conducted from July 1 to August 31, 2022, in public hospitals within Jimma town, Ethiopia. Participants were 305 women who attended childbirth and postpartum services, selected by systematic random sampling. A structured, interviewer-administered questionnaire was used for data collection. Bivariate and multivariable logistic regression analyses were employed to determine the association between variables. Result Of 305 respondents, 301 provided complete responses, resulting in a response rate of 99.1%. Approximately 187 (62%) study participants utilized adequate antenatal care [95% CI: 56.4–67.6]. In multivariate logistic regression women’s empowerment dimensions showed statistically significant association with antenatal care utilization. High general self-efficacy [AOR = 1.89 (1.02–3.50)], high self-esteem [AOR = 3.10 (1.67–5.76)], an internal locus of control [AOR = 2.13 (1.17–3.86)], and labor work participation [AOR = 1.98 (1.06–3.72)]. All these factors were associated with increased antenatal care utilization. Conclusion Women empowerment dimensions have a positive and statistically significant association with antenatal care use. So, to improve recommended antenatal care utilization by mothers, empowerment of women by health professionals, hospitals, and other stakeholders is very important.